Let s co-manage the commons - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Co-managing the Commons. Setting the Stage in Mali and Zambia. T Hilhorst and N Aarnink. Bulletins of the Royal Tropical Institute number 346. 1999. 80 pp. ISBN 90 6832 835 2. Dfl19.50 E 8.85 Royal Tropical Institute, KIT Press, P O Box 95001 10